Serum Meteorin‐like is associated with weight loss in the elderly patients with chronic heart failure. Issue 1 (21st November 2021) - Cai, Juan; Wang, Qi‐Ming; Li, Jia‐Wen; Xu, Fan; Bu, Yun‐Ling; Wang, Man; Lu, Xiang; Gao, Wei
Abstract: Background: Unintentional weight loss (cachexia) has been associated with poor outcomes in chronic heart failure (CHF). Meteorin‐like (Metrnl) is a novel myokine with protective effects on cardiovascular diseases. However, the change of Metrnl concentrations and its role in elderly patients with CHF remains unclear. The aim of this study was to evaluate the association of serum Metrnl with weight loss and outcomes in elderly patients with CHF. Methods: A total of 931 consecutive elderly patients (aged 60 years and older) with CHF and 135 age‐matched and sex‐matched control subjects were enrolled. Serum Metrnl concentration was measured by enzyme‐linked immunosorbent assay. Body weight was measured at baseline and 12 months. Results: Median of serum Metrnl levels was lower in CHF patients when compared with controls [201.31 (184.95–261.16) pg/mL vs. 168.68 (103.15–197.54) pg/mL, P  < 0.001]. Patients with the lowest levels of Metrnl had higher N‐terminal pro brain natriuretic peptide (NT‐proBNP) levels but lower left ventricular eject fraction (LVEF) and estimated glomerular filtration rate ( P  < 0.001). Lower serum Metrnl was associated with a higher risk of >5% weight loss from baseline to 12 months [odds ratio = 6.13, 95% confidence interval (CI) = 2.57–14.62 per log decrease; P  < 0.001]. Serum Metrnl levels were decreased as LVEF decreased ( P  < 0.001) and were positively correlated with LVEF ( r  = 0.267, P  < 0.001) but negatively correlated with NT‐proBNP levels ( r  = −0.257, P  < 0.001). Cox regression analysis suggested that lower serum Metrnl was associated with higher cardiovascular mortality [hazard ratio (HR) = 6.71, 95% CI = 3.41–13.18 per log decrease; P  < 0.001], CHF rehospitalization (HR = 3.07, 95% CI = 1.82–5.17 per log decrease; P  < 0.001), and the combined major adverse cardiac event(s) (MACEs) (HR = 5.38, 95% CI = 3.51–8.25 per log decrease; P  < 0.001). The Kaplan–Meier survival curves showed that low concentration of Metrnl was a prognostic indicator of MACEs in patients with CHF. Conclusions: Our study suggests that lower serum Metrnl level is correlated with weight loss and the severity of cardiac dysfunction in elderly patients with CHF.